Penyampaian Makna Dan Identitas Dari Logo Baru Museum Sumpah Pemuda Jakarta Sebagai Bentuk Komunikasi Visual - Fadhylah Muhammad My; Indria Flowerina (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The Sumpah Pemuda Museum is a historical heritage museum about the struggle of Indonesian youth in delivering the Indonesian youth oath. The new logo of The Sumpah Pemuda Museum can introduce its new visual identity to the public through the logo, the visuals in the logo have visuals such as a fist, three pillars, and a roof combined with three colors, namely red, navy or dark blue, and gray. All of these were designed and won by a logo designer who is a visual communication design student at the Padang Panjang Indonesian Art Institute. In the process of designing a logo, it must comply with the requirements in a logo, namely, unique, easy to remember, flexible and communicative, and conveyed non-verbally. This study discusses how to convey the meaning and identity of the new logo of The Sumpah Pemuda Museum as a form of visual communication. The researcher used 4 informants in which the way of taking the informants used qualitative methods using in-depth interviews, namely the first key informant and the second supporting informant. This study uses a decision-making technique, namely the logo designer has a decision about logo design and semiotics, namely the logo can be used as a sign. The result of this research is the delivery of the meaning and identity of the new logo of the Youth Pledge Museum is by promotion or direct introduction from the museum so that its visual identity can be known by the public, the logo designer also makes a manual graphic book about the logo and the manual graphic book is submitted to The Sumpah Pemuda Museum. And also the meaning of the new logo for the Youth Pledge Museum, namely the struggle of Indonesian youth that expresses energy, enthusiasm, historical values, and pride representing the vision and mission of The Sumpah Pemuda Museum. Keywords : Identity, Logo, Messagges, Visual Communication